The Effect of Employee Professionalism on the Quality of Public Services at the Population and Civil Registration Office in Ambon City - Setitit, Ignasius; Lesnussa, Johny Urbanus (Universitas Negeri Makassar, 2023)
The Ambon City Civil Registry Population Service as a public organization/bureaucracy whose function is to provide public services, is suspected of not optimally providing services that satisfy the user community. This is indicated by the frequent emergence of complaints from the user community about the quality of services provided by the apparatus. So to analyze this problem, the associative method is used using the Pearson Product Moment Correlation formula and to test the significance level of the existing relationship, the t-count formula is used. From the results of the analysis, a correlation value of 0.866 was obtained, then the correlation results were tested for the significance level using the t-count formula, the result of which was 2.839. the effect of variable X on variable Y is 75%. From the results of this analysis it can be said that there is a significant influence between employee professionalism on the quality of public services at the Ambon City Population and Civil Registration Office.